ELECTRONIC TRACTION DC SYSTEM - SYSTEM OF UNSTABLE CURRENT - Sablin, O. I. (Science and Transport Progress, 2007)
The work examines the need of using the power ratio ofd.c.electric rolling-stock as a power characterictic of d.c.traction system. As an example, the results of calculation of the λ value of DE1 electric locomotive in the tractive mode are analysed.